Algorithmic Decision-Making in EU Asylum Procedures - Nistor,Maria Ecaterina (2026)
This thesis examines the growing role of algorithmic and data-driven systems in European Union asylum procedures and explores their implications for legal accountability, procedural fairness, and fundamental rights protection. As migration governance increasingly relies on biometric databases, interoperability frameworks, and automated decision-support systems, questions arise regarding the compatibility of these technologies with the legal safeguards embedded in the Common European Asylum System (CEAS). Using a combined methodology of doctrinal legal analysis and technical illustration, the thesis analyzes how EU migration law, human rights law, data protection law, and the emerging AI regulatory framework govern the use of algorithmic systems in migration administration. Particular attention is paid to procedural guarantees such as individualized assessment, transparency, reasoned decision-making, effective remedies, and meaningful human oversight. The research examines key digital infrastructures including Eurodac, the Schengen Information System (SIS), and the Visa Information System (VIS), as well as interoperability initiatives and biometric matching technologies. The thesis argues that while algorithmic systems are often presented as tools for improving efficiency and consistency, they operate through probabilistic classifications, similarity thresholds, and statistical correlations that may be difficult for affected individuals to understand or challenge. These systems can influence evidentiary assessment and administrative reasoning without fully integrating their underlying logic into legal decision-making processes. The involvement of private technology contractors further complicates questions of accountability and oversight. The research concludes that existing European legal safeguards provide important protections but remain only partially equipped to address the structural challenges posed by algorithmically mediated migration governance. Asylum systems increasingly dependent on digital infrastructures require stronger mechanisms of transparency, explainability, human oversight, and institutional scrutiny to ensure meaningful accountability and effective protection of fundamental rights.
Keywords: Algorithmic Decision-Making; Asylum Law; Common European Asylum System; Artificial Intelligence; Interoperability Systems